Method for improving degradation performance of organic pollutants by activating persulfate based on circulation type electro-catalytic membrane

By combining a boron nitride electrocatalytic membrane loaded with bimetallic nanoparticles with a flow-through electroactivated persulfate reactor, the problem of low mass transfer efficiency in traditional electroactivated persulfate systems is solved, achieving efficient and stable degradation of organic pollutants and improved persulfate utilization, making it suitable for industrial applications.

CN120815565AActive Publication Date: 2025-10-21XI'AN UNIVERSITY OF ARCHITECTURE AND TECHNOLOGY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510937834.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-08
Publication Date
2025-10-21
Estimated Expiration
2045-07-08

AI Technical Summary

Technical Problem

In the prior art, the conventional electro-activated persulfate system results in low utilization efficiency of the persulfate oxidant in a homogeneous system with limited mass transfer, which affects the treatment effect of organic pollutants, and the conventional catalyst is prone to cause secondary pollution of the water environment.

Method used

By using a boron nitride electrocatalytic membrane loaded with bimetallic nanoparticles, a flow-through electroactivated persulfate reactor, and combining it with a membrane catalytic system, the fluid dynamics of the reaction system is optimized, thereby improving the mass transfer efficiency and the controllability of the catalytic reaction.

Benefits of technology

It can efficiently degrade organic pollutants in a wide pH range, significantly improve the utilization rate of persulfate, and achieve rapid degradation of organic pollutants. The reaction device is simple and stable, and is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120815565A_ABST
    Figure CN120815565A_ABST
Patent Text Reader

Abstract

The invention discloses a method for improving degradation performance of organic pollutants based on circulation type electro-catalytic membrane activated persulfate. The method comprises two steps of preparing a boron nitride electro-catalytic membrane loaded with bimetallic nanoparticles and performing circulation type degradation reaction. Compared with a traditional mode, the circulation mode provided by the invention realizes effective coupling of a membrane catalysis system and a traditional electro-activated persulfate system, breaks through the limitation of low mass transfer efficiency, and remarkably improves the utilization rate of persulfate, thereby improving the degradation efficiency of organic pollutants. The circulation type reactor provided by the invention is simple in structure, strong in operability, good in stability and wide in industrial application prospect, the catalyst is not easy to lose, and an efficient, economical and sustainable solution is provided for degradation of organic pollutants.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of environmental remediation materials, relates to the treatment of organic pollutants, and specifically relates to a method for improving the degradation performance of organic pollutants based on persulfate activation of a flow-through electrocatalytic membrane. Background Art

[0002] The long-term presence of organic pollutants in the water environment has become a major problem of water pollution worldwide, especially organic pollutants such as antibiotics, dyes, and drug residues. The development of efficient and environmentally friendly water treatment technologies has become the focus of current research. Advanced oxidation technology based on persulfate is able to generate active species with strong oxidizing ability (such as SO4 •- and • OH), has gradually become an effective method for treating organic pollutants.

[0003] Since the rate at which persulfate self-decomposes to produce active species is low, it is often quickly activated by adding external catalysts or applying external energy. External catalysts include transition metals, carbon-based materials, metal-organic frameworks, etc. Currently, transition metal-based catalysts are recognized as one of the most effective ways to activate persulfate. Monometallic catalysts have poor activation effects due to the lack of synergistic effects between metals, so bimetallic catalysts have become persulfate activators worthy of consideration. In addition, since transition metals easily release metal ions into the water environment when activating persulfate, it is easy to cause secondary pollution of the water environment. Therefore, it is still challenging to find a stable and efficient transition metal-based catalyst to improve the persulfate activation effect while ensuring the stability of the catalyst.

[0004] Electroactivation is another way to activate persulfate by applying external energy, and this method is often used in conjunction with transition metal catalysts to synergistically promote the activation of persulfate, thereby accelerating the degradation of pollutants. That is, a transition metal-based catalyst is loaded on an ordinary electrode substrate to prepare a highly active transition metal-based electrode material. Traditional electroactivated persulfate systems are usually carried out in a homogeneous system with limited mass transfer, which limits the mass transfer efficiency between persulfate, pollutants and electrocatalysts, resulting in low utilization efficiency of the persulfate oxidant, thereby affecting the treatment effect of pollutants. In contrast, catalytic membrane systems can improve the mass transfer efficiency of the reaction system through forced convection, thereby improving the controllability of the catalytic reaction time and the long-term stability of the system. However, how to achieve effective coupling between the catalytic membrane system and the traditional electroactivated persulfate system, and how to achieve effective activation of persulfate by optimizing the fluid dynamics process of the reaction system in order to achieve efficient degradation of pollutants, are still technical problems that need to be overcome. Summary of the Invention

[0005] The object of the present invention is to provide a method for improving the degradation performance of organic pollutants based on flow-through electrocatalytic membrane-activated persulfate. This method constructs a high-efficiency collaborative treatment system by introducing a membrane catalytic system that enhances mass transfer efficiency and effectively coupling it with a traditional electroactivated persulfate system. This method can effectively solve the technical problem that the low mass transfer efficiency in the traditional degradation mode leads to insufficient utilization of persulfate, which is not conducive to its degradation of organic pollutants.

[0006] The present invention adopts the following technical solutions to achieve the above-mentioned invention objectives: A method for improving the degradation performance of organic pollutants by activating persulfate using a flow-through electrocatalytic membrane, wherein the flow-through electrocatalytic membrane is a boron nitride electrocatalytic membrane loaded with bimetallic nanoparticles. The method specifically comprises the following steps: Step 1: preparing a boron nitride electrocatalytic film loaded with bimetallic nanoparticles; Step 1.1, preparation of boron nitride: Boric acid and melamine are dispersed in deionized water and reacted in a constant temperature autoclave. The resulting product is dried, ground, and then pyrolyzed to obtain boron nitride (BN). Step 1.2, preparation of boron nitride loaded with bimetallic nanoparticles: The BN prepared in step 1.1 was dispersed in ethanol, and cobalt chloride hexahydrate and ammonium heptamolybdate tetrahydrate aqueous solution were added at the same time. After mixing, sodium borohydride solution was added. After stirring, the mixture was centrifuged, washed, and dried in sequence. After pyrolysis, bimetallic nanoparticle-loaded boron nitride (CoMo@BN) was obtained. Step 1.3, preparation of CoMo@BN loaded electrocatalytic membrane: The CoMo@BN prepared in step 1.2 was dispersed in ethanol, and conductive acetylene black and polyvinylidene fluoride solution were added. After ultrasonic mixing, the mixture was uniformly distributed on a nylon membrane by negative pressure filtration. After drying, the electrocatalytic membrane loaded with CoMo@BN was obtained. Step 2: Conduct a flow-through degradation reaction: Add persulfate to organic wastewater containing electrolytes and pollutants to form a reaction system; The degradation process is carried out in a flow-through electroactivated persulfate reactor by dead-end filtration with a constant DC voltage applied. The electrocatalytic membrane loaded with CoMo@BN serves as the working electrode, and the platinum wire ring serves as the counter electrode. The reaction system is pumped into the reactor at a constant flow rate through a peristaltic pump to realize a flow-through pollutant degradation process. The reaction time is 60 to 180 minutes.

[0007] Preferably, in step 1.1, the mass ratio of boric acid to melamine is 1:1, and the boric acid concentration is 1.2 M; the temperature in the autoclave is 105°C, and the reaction is carried out for 3 h; the pyrolysis process is as follows: in a nitrogen atmosphere at 5°C·min -1The temperature was raised to 900-1100°C at a rate of 1.5 ℃ and pyrolysis was continued at this temperature for 2-4 h.

[0008] Preferably, in step 1.2, the ratio of the mass of BN to the volume of ethanol is 10 g:1 L; the molar ratio of cobalt chloride hexahydrate to ammonium heptamolybdate tetrahydrate is 8:1, the concentration of cobalt chloride hexahydrate is 0.025 M; the concentration of sodium borohydride solution is 0.1 M; the pyrolysis process is: in a nitrogen atmosphere at 5 ° C·min -1 The temperature was raised to 400°C at a rate of 0.5°C and maintained for 2-4 h.

[0009] Preferably, in step 1.3, the ratio between the mass of CoMo@BN and the volume of ethanol is 15 g:1 L, the mass fraction of the polyvinylidene fluoride is 3-6 wt%, and the mass fraction of the conductive acetylene black is 10-15 wt%.

[0010] Preferably, in step 2, the pollutants are tetracycline, oxytetracycline, chlortetracycline, rhodamine B, methylene blue, methyl orange, and orange G; the concentration of the pollutants is 20 mg·L -1 .

[0011] Preferably, in step 2, the electrolyte is a sodium sulfate solution; the concentration of the electrolyte is 50 mM.

[0012] Preferably, in step 2, the concentration of the persulfate is 0.1-0.5 mM.

[0013] Preferably, in step 2, the pH value of the reaction system is 3-9.

[0014] Preferably, in step 2, the DC voltage is 1-2 V; the flow rate is 1-7 mL·min -1 .

[0015] Compared with the prior art, the beneficial technical effects of the present invention are: (1) The present invention provides a boron nitride electrocatalytic membrane loaded with bimetallic nanoparticles for use in the activation of persulfate, which can efficiently degrade pollutants over a wide pH range and achieve complete removal of pollutants in less than 50 minutes.

[0016] (2) The present invention significantly improves the utilization rate of persulfate, thereby accelerating its degradation efficiency of organic pollutants; this method breaks through the low mass transfer efficiency among pollutants, persulfate and electrocatalysts in the traditional model, optimizes the material exchange process in the reaction system, and thus makes electroactivated persulfate have broad application prospects in the treatment of organic pollutant wastewater.

[0017] (3) The flow-through electroactivated persulfate reactor provided by the present invention has a simple structure and a simple reaction device, which can effectively avoid the loss of catalyst and has good operability and stability. Therefore, it is conducive to industrial production and promotion, and provides a more efficient, economical and sustainable solution for the degradation of organic pollutants. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is the SEM image of CoMo@BN prepared in Example 1.

[0019] Figure 2 This is the XRD test pattern of CoMo@BN prepared in Example 1.

[0020] Figure 3 These are the electrochemical performance test graphs of the BN prepared in Comparative Example 1, the Mo@BN prepared in Comparative Example 2, the Co@BN prepared in Comparative Example 3, and the CoMo@BN electrocatalytic membrane prepared in Example 1; (a) is the CV test graph, and (b) is the EIS test graph.

[0021] Figure 4 The schematic diagram of the reaction device and the structure of the flow-through reactor; in the schematic diagram of the structure of the flow-through reactor, 1, quartz shell, 2, waterproof rubber sealing ring, 3, nylon membrane, 4, electrocatalytic membrane loaded with CoMo@BN, 5, nylon membrane, 6, platinum wire ring; Figure 5 The degradation curve of tetracycline using different electrocatalytic membranes as persulfate activators.

[0022] Figure 6 The degradation curve of tetracycline by the electrocatalytic membrane loaded with CoMo@BN as a persulfate activator at different voltages.

[0023] Figure 7 This is a graph showing the degradation curve of tetracycline by the electrocatalytic membrane loaded with CoMo@BN as a persulfate activator under different persulfate concentrations.

[0024] Figure 8 The degradation curve of tetracycline by the electrocatalytic membrane loaded with CoMo@BN as a persulfate activator under different flow rate conditions.

[0025] Figure 9 The degradation curve of tetracycline by the electrocatalytic membrane loaded with CoMo@BN as a persulfate activator under different pH conditions.

[0026] Figure 10 This is a system stability test diagram for the activation of persulfate by a flow-through electrocatalytic membrane loaded with CoMo@BN for the degradation of organic pollutants.

[0027] Figure 11Figure 2 is the efficiency diagram of persulfate activation by flow-through electrocatalytic membrane loaded with CoMo@BN for degradation of different types of organic pollutants.

[0028] Figure 12 Comparison of the degradation performance of tetracycline by CoMo@BN-loaded electrocatalytic membrane as persulfate activator in flow-through and traditional modes; (a) is the degradation curve, and (b) is the first-order rate constant k The fitting diagram of .

[0029] Figure 13 This is a comparison chart of the persulfate utilization rate of the CoMo@BN-loaded electrocatalytic membrane as a persulfate activator in the flow-through mode and the traditional mode.

[0030] Figure 14 This is a comparison chart of the TOC removal efficiency of the CoMo@BN-loaded electrocatalytic membrane as a persulfate activator for pollutant solutions in the flow-through mode and the traditional mode. DETAILED DESCRIPTION

[0031] The technical solution of the present invention is further described below in conjunction with embodiments.

[0032] It should be noted that, unless otherwise specified, all raw materials used in the present invention are raw materials known in the art.

[0033] In accordance with the above technical solution, specific embodiments of the present invention are given below. It should be noted that the present invention is not limited to the following specific embodiments, and all equivalent changes made on the basis of the technical solution of this application fall within the protection scope of the present invention. Example 1

[0034] A method for improving the degradation performance of organic pollutants by activating persulfate using a flow-through electrocatalytic membrane, wherein the flow-through electrocatalytic membrane is a boron nitride electrocatalytic membrane loaded with bimetallic nanoparticles. The method specifically comprises the following steps: Step 1: Prepare a boron nitride (CoMo@BN) electrocatalytic film loaded with bimetallic nanoparticles; Step 1.1, preparation of boron nitride (BN): 7.42 g of boric acid and 7.42 g of melamine were added to 100 mL of deionized water, and the mixed solution was placed in an autoclave and reacted at 105 °C for 3 h. The obtained product was dried in an oven at 60 °C for 24 h. Subsequently, the dried flakes were ground uniformly and placed in a tube furnace and heated at 5 °C·min in a nitrogen atmosphere. -1 The temperature was raised to 1000°C at a rate of 0.1% and maintained for 3 h to obtain BN; Step 1.2, preparation of boron nitride loaded with bimetallic nanoparticles (CoMo@BN): The BN (0.5 g) prepared in step 1.1 was dispersed in 50 mL of ethanol, referred to as solution A. Meanwhile, 0.476 g of cobalt chloride hexahydrate and 0.309 g of ammonium heptamolybdate tetrahydrate (molar ratio 8:1) were dissolved in 80 mL of deionized water, referred to as solution B. Solutions A and B were mixed and magnetically stirred for 30 min. Then, 20 mL of sodium borohydride solution (0.1 M) was added dropwise. After continuous magnetic stirring for 2 h, the mixture was centrifuged and washed three times with ethanol and deionized water, respectively, and placed in an oven at 60°C for 24 h. The resulting powder was then evaporated at 5 °C min in a nitrogen atmosphere. -1 The temperature was raised to 400°C at a rate of 1000 ℃ and maintained for 3 h to obtain boron nitride CoMo@BN loaded with bimetallic nanoparticles; Step 1.3, preparation of CoMo@BN loaded electrocatalytic membrane: 15 mg of the CoMo@BN prepared in step 1.2 was dispersed in ethanol and ultrasonically treated for 10 min. Subsequently, conductive acetylene black (12 wt%) and polyvinylidene fluoride (5 wt%) were added, and the mixture was ultrasonically treated for another 10 min. The resulting mixture was then loaded onto a nylon membrane by negative pressure filtration and dried at 60°C for 24 h to obtain a CoMo@BN-loaded electrocatalytic membrane.

[0035] The material prepared in step 1 of this embodiment is characterized as follows: from Figure 1 It can be observed in the SEM image in that CoMo@BN shows a layer of flocculent material loaded on BN with a rough surface and irregular cavity structure.

[0036] Figure 2 The XRD pattern of CoMo@BN is shown below. A characteristic peak is observed at 26.7°, corresponding to BN (PDF#45-0895). In addition, characteristic peaks corresponding to the (100) and (102) crystal planes of MoO2 (PDF#50-0739) appear at 36.5° and 53.8°, respectively, and characteristic peaks corresponding to the (111) and (200) crystal planes of Co (PDF#15-0806) appear at 44.2° and 51.5°, respectively. This clearly shows that the main components of the active material supported on the BN surface are Co and MoO2.

[0037] Figure 3 The CV curve of CoMo@BN in (a) shows the largest internal area, indicating higher double-layer capacitance, larger charge storage capacity, and more superior redox properties. Figure 3 (b) shows that the Nyquist plot of CoMo@BN exhibits a smaller semicircle, indicating that it has the lowest charge transfer resistance.

[0038] Step 2: Perform flow-through degradation reaction: Persulfate was added to a total of 100 mL of a solution containing 50 mM Na2SO4 (electrolyte) and 20 mg·L -1 A reaction system was formed in tetracycline-containing organic wastewater with a persulfate concentration of 0.4 mM and a natural pH of 7. The degradation experiments were conducted in a flow-through reactor with an effective reaction area of ​​3 cm × 3 cm. A CoMo@BN-loaded electrocatalytic membrane served as the working electrode, and a platinum wire loop served as the counter electrode. A constant DC voltage of 1.5 V was applied. The reaction system was pumped at a rate of 5 mL / min at room temperature (25°C) using a peristaltic pump. -1 The solution is pumped into the reactor at a flow rate of 100 μg / min. The solution flows from bottom to top through the reactor, ensuring that the electrodes are fully immersed in the solution. This is a dead-end filtration. The treated solution is pumped back into the original container, forming a circulating flow reactor. The reaction time is 60 minutes.

[0039] Reactor structure and reaction device such as Figure 4 As shown in the figure, the device utilizes a top-to-bottom flow structure with a quartz shell forming the reaction chamber, offering excellent corrosion resistance and visibility. Two electrodes are mounted parallel to each other within the chamber, with the electrodes extending outside to connect to a DC power supply. The electrocatalytic membrane anode is covered with a nylon membrane on both the top and bottom sides to prevent catalyst loss and promote uniform liquid flow. Thick waterproof rubber seals are placed on both sides of the electrodes, providing both sealing and insulation between the electrodes.

[0040] In this embodiment, during the degradation reaction, the tetracycline concentration in the reaction system was sampled at fixed times to test. After the degradation reaction was completed, a curve was drawn with the reaction time as the horizontal axis and the ratio of the tetracycline concentration before and after degradation of the reaction system as the vertical axis, as shown in FIG. Figure 5 shown.

[0041] Comparative Example 1 This comparative example provides a method for degrading organic pollutants by activating persulfate based on a flow-through electrocatalytic membrane. The method is basically the same as that in Example 1, with the only difference being that: in step 1, a BN-loaded electrocatalytic membrane is prepared. Step 1.1 is the same as in Example 1 for preparing BN, and step 1.2 in Example 1 is omitted. The BN-loaded electrocatalytic membrane is prepared by referring to the method of step 1.3 in Example 1. In step 2, the "BN-loaded electrocatalytic membrane" is used to replace the "CoMo@BN-loaded electrocatalytic membrane" in Example 1. In this example, the final tetracycline degradation curve is as shown in FIG. Figure 5 shown.

[0042] Comparative Example 2 This comparative example provides a method for degrading organic pollutants by activating persulfate based on a flow-through electrocatalytic membrane. The method is basically the same as Example 1, with the only difference being that: in step 1, an electrocatalytic membrane loaded with Mo@BN is prepared, and the step 1.1 for preparing BN is the same as in Example 1; in step 1.2, the raw material cobalt chloride hexahydrate is omitted, and Mo@BN is prepared with reference to step 1.2 in Example 1; an electrocatalytic membrane loaded with Mo@BN is prepared with reference to the method of step 1.3 in Example 1; in step 2, "an electrocatalytic membrane loaded with Mo@BN" is used to replace the "electrocatalytic membrane loaded with CoMo@BN" in Example 1. In this example, the final tetracycline degradation curve drawn is as follows: Figure 5 shown.

[0043] Comparative Example 3 This comparative example provides a method for degrading organic pollutants by activating persulfate based on a flow-through electrocatalytic membrane. The method is basically the same as Example 1, with the only difference being that: in step 1, a Co@BN-loaded electrocatalytic membrane is prepared, and the step 1.1 for preparing BN is the same as in Example 1; in step 1.2, the raw material ammonium heptamolybdate tetrahydrate is omitted, and Co@BN is prepared with reference to step 1.2 in Example 1; a Co@BN-loaded electrocatalytic membrane is prepared with reference to the method of step 1.3 in Example 1; in step 2, "Co@BN-loaded electrocatalytic membrane" is used to replace the "CoMo@BN-loaded electrocatalytic membrane" in Example 1. In this example, the final tetracycline degradation curve drawn is as follows: Figure 5 shown. Example 2

[0044] This example provides a method for improving the degradation performance of organic pollutants by activating persulfate based on a flow-through electrocatalytic membrane. In step 2 of this method, "a constant DC voltage of 1 V is applied", and the other processes remain the same as in Example 1. In this example, the final tetracycline degradation curve is as follows: Figure 6 shown. Example 3

[0045] This example provides a method for improving the degradation performance of organic pollutants by activating persulfate based on a flow-through electrocatalytic membrane. In step 2 of this method, "a constant DC voltage of 2 V is applied", and the other processes remain the same as in Example 1. In this example, the final tetracycline degradation curve is as follows: Figure 6 shown.

[0046] Comparative Example 4 This comparative example provides a method for enhancing the degradation of organic pollutants based on persulfate activated by a flow-through catalytic membrane. In step 2 of this method, "no constant DC voltage is applied (open circuit state)", and the other processes remain the same as in Example 1. In this example, the final tetracycline degradation curve is as follows Figure 6 shown. Example 4

[0047] This example provides a method for improving the degradation performance of organic pollutants by activating persulfate based on a flow-through electrocatalytic membrane. In step 2 of this method, the concentration of persulfate in the reaction system is 0.3 mM, and the other processes are the same as in Example 1. In this example, the final tetracycline degradation curve is as follows: Figure 7 shown. Example 5

[0048] This example provides a method for improving the degradation performance of organic pollutants by activating persulfate based on a flow-through electrocatalytic membrane. In step 2 of this method, the concentration of persulfate in the reaction system is 0.5 mM, and the other processes are the same as in Example 1. In this example, the final tetracycline degradation curve is as follows: Figure 7 shown. Example 6

[0049] This example provides a method for improving the degradation performance of organic pollutants by activating persulfate using a flow-through electrocatalytic membrane. In step 2 of this method, the concentration of persulfate in the reaction system is 0.1 mM, and the other processes are the same as in Example 1. In this example, the final tetracycline degradation curve is as follows: Figure 7 shown.

[0050] Comparative Example 5 This comparative example provides a method for degrading organic pollutants based on a flow-through electrocatalytic membrane. In step 2 of this method, "the reaction system does not contain persulfate", and the other processes are the same as in Example 1. In this example, the final tetracycline degradation curve is as follows Figure 7 shown. Example 7

[0051] This example provides a method for improving the degradation performance of organic pollutants by activating persulfate using a flow-through electrocatalytic membrane. In step 2 of this method, the reaction system is pumped at a rate of 7 mL·min -1 The flow rate was pumped into the reactor. Other processes were the same as in Example 1. In this example, the final tetracycline degradation curve was drawn as shown in Figure 8 shown. Example 8

[0052] This example provides a method for improving the degradation performance of organic pollutants by activating persulfate based on a flow-through electrocatalytic membrane. In step 2 of this method, the reaction system is pumped at a rate of 3 mL·min -1The flow rate was pumped into the reactor. Other processes were the same as in Example 1. In this example, the final tetracycline degradation curve was drawn as shown in Figure 8 shown. Example 9

[0053] This example provides a method for improving the degradation performance of organic pollutants by activating persulfate based on a flow-through electrocatalytic membrane. In step 2 of this method, the reaction system is pumped at a rate of 1 mL·min -1 The flow rate was pumped into the reactor. Other processes were the same as in Example 1. In this example, the final tetracycline degradation curve was drawn as shown in Figure 8 shown. Example 10

[0054] This example provides a method for improving the degradation performance of organic pollutants by activating persulfate based on a flow-through electrocatalytic membrane. In step 2 of this method, "the pH value of the reaction system is adjusted to 3 using dilute H2SO4", and the other processes remain the same as in Example 1. In this example, the final tetracycline degradation curve is as follows: Figure 9 shown. Example 11

[0055] This example provides a method for improving the degradation performance of organic pollutants by activating persulfate based on a flow-through electrocatalytic membrane. In step 2 of this method, "the pH value of the reaction system is adjusted to 5 using dilute H2SO4", and the other processes remain the same as in Example 1. In this example, the final tetracycline degradation curve is as follows: Figure 9 shown. Example 12

[0056] This example provides a method for improving the degradation performance of organic pollutants by activating persulfate based on a flow-through electrocatalytic membrane. In step 2 of this method, "the pH value of the reaction system is adjusted to 9 using NaOH", and the other processes remain the same as in Example 1. In this example, the final tetracycline degradation curve is as follows: Figure 9 shown. Example 13

[0057] This example provides a method for improving the degradation performance of organic pollutants by activating persulfate using a flow-through electrocatalytic membrane. In step 2 of this method, "the treated solution is no longer pumped back into the original container, forming a continuous flow-through reaction device with a reaction time of 1080 min." The other processes remain consistent with Example 1.

[0058] In this embodiment, during the degradation reaction, the tetracycline concentration in the reaction system was sampled every 60 minutes at the outlet. After the degradation reaction was completed, a bar graph was drawn with the reaction time as the horizontal axis and the degradation efficiency of tetracycline before and after degradation of the reaction system as the vertical axis, as shown in FIG. Figure 10 shown. Example 14

[0059] This embodiment provides a method for improving the degradation performance of organic pollutants by activating persulfate based on a flow-through electrocatalytic membrane. In step 2 of this method, "the pollutants are oxytetracycline, chlortetracycline, rhodamine B, methylene blue, methyl orange, and orange G", and the other processes remain consistent with Example 1.

[0060] In this embodiment, after the degradation reaction is completed, the concentration of pollutants in the reaction system is sampled and tested, and the degradation efficiency of the pollutants before and after degradation of the reaction system is calculated, and a bar graph is drawn, such as Figure 11 shown. Example 15

[0061] This embodiment provides a method for improving the degradation performance of organic pollutants by activating persulfate based on a flow-through electrocatalytic membrane. In step 2 of the method, a magnetic stirrer is used to stir the reaction system of step 2 at a speed of 250 rpm, and a peristaltic pump is used to pump the reaction system at a speed of 5 mL·min -1 The flow rate was pumped into the reactor, and the other processes remained the same as in Example 1.

[0062] In this embodiment, during the degradation reaction, samples were taken at fixed times to test the tetracycline concentration and persulfate content in the reaction system. After the degradation reaction was completed, a curve was drawn with the reaction time as the horizontal axis and the ratio of the tetracycline concentration before and after degradation of the reaction system as the vertical axis, as shown in FIG. Figure 12 (a) shows the calculated first-order reaction rate constant k like Figure 12 After the degradation reaction is completed, a curve is drawn with the reaction time as the horizontal axis and the utilization efficiency of persulfate before and after degradation of the reaction system as the vertical axis, as shown in Figure 2. Figure 12 shown.

[0063] Comparative Example 6 This comparative example provides a method for degrading organic pollutants by electroactivating persulfate, which specifically comprises the following steps: Step 1: preparing a boron nitride (CoMo@BN) electrocatalytic film loaded with bimetallic nanoparticles, which is consistent with Example 1; Step 2: Degradation reaction: Persulfate was added to a total of 100 mL of a solution containing 50 mM Na2SO4 (electrolyte) and 20 mg·L-1 A reaction system was formed in tetracycline-containing organic wastewater with a persulfate concentration of 0.4 mM and a natural pH of 7. The degradation process was carried out in a 200 mL beaker containing the reaction system. A CoMo@BN-loaded electrocatalytic membrane served as the working electrode, and a platinum wire loop served as the counter electrode. The two electrodes were placed vertically in the solution with a distance of 2 cm between them. A constant DC voltage of 1.5 V was applied. The reaction system was stirred at 250 rpm using a magnetic stirrer at room temperature (25°C) for 60 minutes.

[0064] In this comparative example, during the degradation reaction, samples were taken at fixed times to test the tetracycline concentration and persulfate content in the reaction system. After the degradation reaction was completed, a curve was drawn with the reaction time as the horizontal axis and the ratio of the tetracycline concentration before and after degradation of the reaction system as the vertical axis, as shown in FIG. Figure 12 (a) shows the calculated first-order reaction rate constant k like Figure 12 After the degradation reaction is completed, a curve is drawn with the reaction time as the horizontal axis and the utilization efficiency of persulfate before and after degradation of the reaction system as the vertical axis, as shown in Figure 2. Figure 13 shown. Example 16

[0065] This example provides a method for improving the degradation performance of organic pollutants by activating persulfate using a flow-through electrocatalytic membrane. In step 2 of this method, the reaction time is 180 min, and the other processes remain consistent with Example 15.

[0066] In this embodiment, during the degradation reaction, samples were taken at fixed times to test the total organic carbon (TOC) content in the reaction system. After the degradation reaction was completed, a curve was plotted with the reaction time as the horizontal axis and the TOC removal efficiency of the reaction system before and after degradation as the vertical axis, as shown in Figure 2. Figure 14 shown.

[0067] Comparative Example 7 This comparative example provides a method for degrading organic pollutants by electro-activating persulfate. In step 2 of this method, the reaction time is 180 min, and the other processes remain the same as those in comparative example 6.

[0068] In this comparative example, during the degradation reaction, samples were taken at fixed times to test the total organic carbon (TOC) content in the reaction system. After the degradation reaction was completed, a curve was drawn with the reaction time as the horizontal axis and the TOC removal efficiency of the reaction system before and after degradation as the vertical axis, as shown in the figure below. Figure 14 shown.

[0069] The following conclusions are obtained from the above examples and comparative examples: (A) From Comparative Examples 1 to 3 and Example 1, it can be seen that: Depend on Figure 5 When bimetallic nanoparticles were loaded onto boron nitride (CoMo@BN), the electrocatalytic membrane-activated persulfate achieved 100% tetracycline degradation within a reaction time of less than 50 minutes. When metal-free or single-metal nanoparticles were loaded onto boron nitride (BN, Mo@BN, and Co@BN), the electrocatalytic membrane-activated persulfate achieved tetracycline degradation rates of 60.05%, 78.36%, and 92.08%, respectively, within a reaction time of 60 minutes. These results demonstrate that transition metal Co and Mo nanoparticles enhance the catalytic efficiency of persulfate, and the synergistic effect of the bimetallic nanoparticles further enhances catalytic efficiency, leading to efficient tetracycline degradation.

[0070] (B) From Comparative Example 4 and Examples 1 to 3, it can be seen that: Depend on Figure 6 It can be seen that when no voltage is applied to the CoMo@BN electrocatalytic membrane, the degradation rates of tetracycline are 82.95%, 88.93%, 100%, and 98.13%, respectively, when voltages of 1 V, 1.5 V, and 2 V are applied. The results show that the degradation efficiency of tetracycline gradually increases with the increase in the applied voltage. However, when the voltage reaches 1.5 V, further increasing the voltage has an adverse effect on the degradation efficiency, and 1.5 V is the optimal voltage value.

[0071] (C) From Comparative Example 5, Example 1 and Examples 4-6, it can be seen that: Depend on Figure 7 It can be seen that when the persulfate concentration in the reaction system was 0.3 mM, 0.4 mM, and 0.5 mM, respectively, the degradation efficiency of tetracycline reached 94.03%, 100%, and 98.93% after 60 minutes of reaction. The degradation efficiency was only 54.05% and 78.02% when no persulfate was added or only 0.1 mM persulfate was added. These results show that when the CoMo@BN-loaded electrocatalytic membrane is used as an activator, the addition of higher persulfate concentrations within a certain range will improve the degradation efficiency of the pollutant, but excessively high concentrations will be detrimental to pollutant degradation.

[0072] (D) From Example 1 and Examples 7-9, it can be seen that: Depend on Figure 8 It can be seen that when the peristaltic pump pumps the reaction system solution into the reactor, the flow rate is 1 mL·min -1 、3mL·min -1 、5 mL·min -1 and 7 mL·min -1The degradation efficiency of tetracycline was 63.24%, 86.24%, 100% and 100% respectively. The results showed that the degradation efficiency of tetracycline increased with the continuous increase of flow rate. Considering the energy consumption, 5 mL·min -1 For the optimal flow rate.

[0073] (E) From Example 1 and Examples 10-12, it can be seen that: Depend on Figure 9 It can be seen that the degradation efficiency of tetracycline is 98.05%, 97.16%, 100%, and 97.71% at pH 3, 5, 7, and 9, respectively. The results show that the degradation rate of tetracycline in the reaction system exceeds 97% over a wide pH range, indicating that the reaction system can adapt to a wide pH range.

[0074] (F) From Example 13, it can be seen that: Depend on Figure 10 It can be seen that when the CoMo@BN-loaded electrocatalytic membrane is used as a persulfate activator, the degradation efficiency of tetracycline in the system is not less than 93% after 1080 min of operation in continuous flow mode, indicating that the reaction system has good operational stability.

[0075] (G) From Example 14, it can be seen that: Depend on Figure 11 When the CoMo@BN-loaded electrocatalytic membrane was used as a persulfate activator, the degradation efficiencies for oxytetracycline (OTC), chlortetracycline (CTC), rhodamine B (RhB), methylene blue (MB), methyl orange (MO), and orange G (OG) were 94.63%, 96.42%, 100%, 100%, 99.84%, and 100%, respectively, within 60 minutes under flow-through mode. These results demonstrate that the degradation rates of the CoMo@BN-loaded electrocatalytic membrane for the above pollutant reaction systems exceeded 94%, demonstrating the membrane's suitability for the degradation of a wide range of pollutants.

[0076] (H) From Comparative Example 6 and Example 15, it can be seen that: Depend on Figure 12 (a) and 12 (b) show that when the electrocatalytic membrane loaded with CoMo@BN is used as a persulfate activator, the degradation efficiency of tetracycline in the flow mode is 100% within 60 min, and the first-order rate constant is k 0.159 min -1 The degradation efficiency of tetracycline in the traditional degradation mode is only 85.71%, and the first-order rate constant is k 0.089 min -1 The results show that the use of Figure 4The flow pattern constructed by the reactor and reaction device significantly improves the catalytic efficiency of persulfate, accelerates the degradation rate of tetracycline, and increases the degradation efficiency to 100%.

[0077] Depend on Figure 13 It can be seen that when the electrocatalytic membrane loaded with CoMo@BN is used as a persulfate activator, the utilization rate of persulfate in the circulation mode and the traditional degradation mode continues to increase with the extension of reaction time. The utilization rate of persulfate in the reaction system in the circulation mode is always higher than that in the traditional degradation mode. Finally, the utilization rate of persulfate in the circulation mode within 60 minutes is 93.69%, while the value in the traditional degradation mode is 73.89%. This result shows that the electrocatalytic membrane loaded with CoMo@BN is an efficient activator of persulfate, and compared with the traditional degradation mode, the utilization rate of persulfate in the circulation mode is 93.69%. Figure 4 The circulation mode constructed by the reactor and the reaction device can significantly improve the utilization rate of persulfate.

[0078] (I) From Comparative Example 7 and Example 16, it can be seen that: Depend on Figure 14 It can be seen that when the electrocatalytic membrane loaded with CoMo@BN is used as a persulfate activator, the TOC removal rate of the reaction system in the flow mode is always higher than that in the traditional degradation mode. In the final 180 minutes, the TOC removal rate of the reaction system in the flow mode is 77.51%, but it is only 54.36% in the traditional degradation mode. This result shows that the use of Figure 4 The circulation mode constructed by the reactor and reaction device has a high TOC removal rate for the reaction system and shows a higher removal effect than the traditional degradation mode.

[0079] Combining the results of (A) to (E) above, we conclude that the bimetallic nanoparticle-loaded boron nitride (CoMo@BN) electrocatalytic membrane can serve as a highly efficient persulfate activator for tetracycline degradation. The optimal reaction system ultimately determined by this invention is: a tetracycline concentration of 20 mg·L -1 The concentration of persulfate was 0.4 mM, the applied anode voltage was 1.5 V, and the peristaltic pump was used to pump the solution into the reactor at a rate of 5 mL min -1 , and the reaction pH range it can adapt to is 3~9.

[0080] Based on the results of (F) to (G), the following conclusions are drawn: Boron nitride (CoMo@BN) electrocatalytic membrane loaded with bimetallic nanoparticles is used as a persulfate activator. Figure 4 The flow mode constructed by the reactor and reaction device has good operating stability and is suitable for the degradation of a wide range of different types of pollutants.

[0081] Based on the results of (H) to (I) above, the following conclusions were drawn: When the electrocatalytic membrane loaded with CoMo@BN was used as a persulfate activator, compared with the traditional degradation mode, the Figure 4 The flow pattern constructed by the reactor and reaction device significantly improves the degradation efficiency and rate of pollutants, TOC removal rate and utilization rate of persulfate.

Claims

1. A method for improving the degradation performance of organic pollutants based on persulfate activation using a flow-through electrocatalytic membrane, characterized in that: The flow-through electrocatalytic membrane is a boron nitride electrocatalytic membrane loaded with bimetallic nanoparticles. The method specifically comprises the following steps: Step 1: preparing a boron nitride electrocatalytic film loaded with bimetallic nanoparticles; Step 1.1, preparation of boron nitride: Boric acid and melamine are dispersed in deionized water and then reacted in a constant temperature autoclave. The resulting product is dried, ground, and then pyrolyzed to obtain boron nitride (BN). Step 1.2, preparation of boron nitride loaded with bimetallic nanoparticles: The BN prepared in step 1.1 was dispersed in ethanol, and cobalt chloride hexahydrate and ammonium heptamolybdate tetrahydrate aqueous solution were added at the same time. After mixing, sodium borohydride solution was added. After stirring, the mixture was centrifuged, washed, and dried in sequence. After pyrolysis, bimetallic nanoparticle-loaded boron nitride (CoMo@BN) was obtained. Step 1.3, preparation of CoMo@BN loaded electrocatalytic membrane: The CoMo@BN prepared in step 1.2 was dispersed in ethanol, and conductive acetylene black and polyvinylidene fluoride solution were added. After ultrasonic mixing, the mixture was uniformly distributed on a nylon membrane by negative pressure filtration. After drying, the electrocatalytic membrane loaded with CoMo@BN was obtained. Step 2: Conduct a flow-through degradation reaction: Add persulfate to organic wastewater containing electrolytes and pollutants to form a reaction system; The degradation process is carried out in a flow-through electroactivated persulfate reactor by dead-end filtration with a constant DC voltage applied. The electrocatalytic membrane loaded with CoMo@BN serves as the working electrode, and the platinum wire ring serves as the counter electrode. The reaction system is pumped into the reactor at a constant flow rate through a peristaltic pump to realize a flow-through pollutant degradation process. The reaction time is 60 to 180 minutes.

2. The method for improving the degradation performance of organic pollutants by activating persulfate using a flow-through electrocatalytic membrane according to claim 1, wherein: In step 1.1, the mass ratio of boric acid to melamine is 1:1; the temperature in the autoclave is 105°C, the boric acid concentration is 1.2 M, and the reaction is carried out for 3 h; the pyrolysis process is as follows: in a nitrogen atmosphere, the temperature is 5°C·min -1 The temperature was raised to 900-1100°C at a rate of 1.5-2.0 °C and pyrolysis was continued at this temperature for 2-4 h.

3. The method for improving the degradation performance of organic pollutants by activating persulfate using a flow-through electrocatalytic membrane according to claim 1, wherein: In step 1.2, the ratio of the mass of BN to the volume of ethanol is 10 g:1 L; the molar ratio of cobalt chloride hexahydrate to ammonium heptamolybdate tetrahydrate is 8:1, the concentration of cobalt chloride hexahydrate is 0.025 M; the concentration of sodium borohydride solution is 0.1 M; the pyrolysis process is: in a nitrogen atmosphere at 5 °C·min -1 The temperature was raised to 400°C at a rate of 0.5°C and maintained for 2-4 h.

4. The method for improving the degradation performance of organic pollutants by activating persulfate using a flow-through electrocatalytic membrane according to claim 1, wherein: In step 1.3, the ratio of the mass of CoMo@BN to the volume of ethanol is 15 g:1 L, the mass fraction of the polyvinylidene fluoride is 3-6 wt %, and the mass fraction of the conductive acetylene black is 10-15 wt %.

5. The method for improving the degradation performance of organic pollutants by activating persulfate using a flow-through electrocatalytic membrane according to claim 1, wherein: In step 2, the pollutants are tetracycline, oxytetracycline, chlortetracycline, rhodamine B, methylene blue, methyl orange, and orange G; the concentration of the pollutants is 20 mg·L -1 .

6. The method for improving the degradation performance of organic pollutants by activating persulfate using a flow-through electrocatalytic membrane according to claim 1, wherein: In step 2, the electrolyte is sodium sulfate; the concentration of the electrolyte is 50 mM.

7. The method for improving the degradation performance of organic pollutants by activating persulfate using a flow-through electrocatalytic membrane according to claim 1, wherein: In step 2, the concentration of the persulfate is 0.1-0.5 mM.

8. The method for improving the degradation performance of organic pollutants by activating persulfate using a flow-through electrocatalytic membrane according to claim 1, wherein: In step 2, the pH value of the reaction system is 3-9.

9. The method for improving the degradation performance of organic pollutants by activating persulfate using a flow-through electrocatalytic membrane according to claim 1, wherein: In step 2, the DC voltage is 1-2 V; the flow rate is 1-7 mL·min -1 .

Citation Information

Patent Citations

  • Porous boron nitride loaded iron nano material as well as preparation method and application thereof

    CN111111741A

  • Preparation method and application of cobalt nanoparticle / boron nitride composite material

    CN114522713A

  • Spiny molybdenum dioxide / molybdenum carbide / carbon self-supporting nano electro-catalysis hydrogen evolution material as well as preparation method and application of spiny molybdenum dioxide / molybdenum carbide / carbon self-supporting nano electro-catalysis hydrogen evolution material

    CN115505955A